A human-machine adversarial scoring framework for urban perception assessment using street-view images. Issue 12 (2nd December 2019) - Yao, Yao; Liang, Zhaotang; Yuan, Zehao; Liu, Penghua; Bie, Yongpan; Zhang, Jinbao; Wang, Ruoyu; Wang, Jiale; Guan, Qingfeng
ABSTRACT: Though global-coverage urban perception datasets have been recently created using machine learning, their efficacy in accurately assessing local urban perceptions for other countries and regions remains a problem. Here we describe a human-machine adversarial scoring framework using a methodology that incorporates deep learning and iterative feedback with recommendation scores, which allows for the rapid and cost-effective assessment of the local urban perceptions for Chinese cities. Using the state-of-the-art Fully Convolutional Network (FCN) and Random Forest (RF) algorithms, the proposed method provides perception estimations with errors less than 10%. The driving factor analysis from both the visual and urban functional aspects demonstrated its feasibility in facilitating local urban perception derivations. With high-throughput and high-accuracy scorings, the proposed human-machine adversarial framework offers an affordable and rapid solution for urban planners and researchers to conduct local urban perception assessments.